Risk Factors of Supply Chain in Biopharmaceutical Companies in Iran - Hadi Abbasian; Reza Yousefi-Zenouz; Akbar Abdollahiasl; Mahdi Toroski; Shekoufeh Nikfar; Mohammadreza Siahi-Shadbad; Abbas Kebriaeezadeh (Tabriz University of Medical Sciences, 2021)
Background: Supply chain risk management can help companies detect potential hazards,mitigate potential risks, and thereby increase supply chain efficiency. The biopharmaceuticalindustry in Iran has a generic-based pharmerging market. Therefore, identifying risksassociated with the supply chain of those drugs can significantly boost the possibility of successof biopharmaceutical companies. This study is conducted to determine the supply chain riskfactors of biopharmaceuticals companies in Iran. Methods: The current research work is a qualitative-quantitative study. A systematic review andinterview with experts (n=14) were conducted to identify potential supply chain risks in thebiopharmaceutical industries. To determine the significance of identified risks, Fuzzy screeningmethod was employed to collect the opinions of experts (n=16) in the biopharmaceuticalindustries. Results: By systematic review and interviews with the biopharmaceutical industry experts, 100 potential risks in the biopharmaceutical industry supply chain were identified. These risks weredivided into two general categories namely macro and micro risks. Based on experts' judgment,77 out of 100 identified risks were eliminated and 23 significant risks were determined. Themost important risks are the Ministry of health (as the regulatory body) conflict of interest, USsanctions, lack of domestic suppliers of essential materials, pseudo-productivity, and moneytransfer related to the bank's sanctions. Conclusion: Due to the multitude of present risks and the impossibility of controlling all ofthem, it is recommended that managers and producers focus more on controlling the identifiedsignificant risks.